Malária vivax no estado do Pará: influência de polimorfismos nos genes TNFA, IFNG e IL10 associados à resposta imune humoral e ancestralidade genômica - Furini, Adriana Antônia da Cruz (2016)
Malaria is one of the mayor cause of morbidity and mortality in tropical and subtropical countries. Objectives: To evaluate the influence of genetic ancestry in the distribution of polymorphisms in genes involved in the immune response and antibody levels against proteins expressed in the merozoite stage of Plasmodium vivax. Material and Methods: To evaluated 90 patients with vivax malaria and 51 non-infected patients from Goianésia do Pará, northern Brazil. Nine single nucleotide polymorphisms (SNPs) in the genes: TNFA, IL-10 INFG were genotyped by PCR-ASO or RFLP-PCR. The genetic ancestry for three ethnic groups (African, European and American Indian) were categorized using 48 INDELs. The responses of specific antibodies against the C-terminal proteins (MSP-119) MSP-1, BPD and AMA-1 of P. vivax were determined by ELISA. Results: There were no differences in ancestry proportions in most SNPs investigated only for TNF-308A allele and European ancestry. No significant association was observed between the allele and genotype frequencies of the SNPs between the groups investigated. There was no significant difference in the levels of IgG antibodies to the studied polymorphisms. Conclusions: These results indicated that the polymorphisms in the TNFA, INFG e IL10 genes can not influence the anti-merozoites immune response of P. vivax. We discussed the immunogenetic profile involved in the humoral immune response in malaria vivax in an endemic area of the Brazilian Amazon.